Peran Keluarga Terhadap Keputusan Remaja Menikah Dini - Astika, Nova; Apriani, Lia Arian; Yulastini, Fitria; Fajriani, Evalina; Wiguna, Reza Indra (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2025)
Indonesia faces a significant challenge with child marriage, ranking second highest in ASEAN after Cambodia. This alarming trend has seen a concerning increase, highlighting the urgent need for effective interventions. In 2020 alone, NTB Province recorded 805 cases of underage marriage, emphasizing the critical nature of this issue within the region. This study aims to investigate the crucial role of family and the level of adolescent knowledge regarding early marriage in contributing to this concerning phenomenon. This study employed an analytical observational method with a cross-sectional design, conducted at SMPN 02 Batukliang in Central Lombok Regency, involving 98 adolescent students as participants. The results of the study revealed that 39.8% of respondents belonged to families with either